PENGEMBANGAN MEDIA PEMBELAJARAN POP UP BOOK BERBANTUAN QR CODE MATERI TRADISI DAN BUDAYA MASYARAKAT DI SEKITARKU - Nur Futri Sidh Ahtun; Ratih Purnamasari; Tatang Muhajang (STKIP Subang, 2025)
Pop pop up book is a type of three-dimensional book that shows paper elements that can move, stand up, or appear when the page is opened. However, at SDN Situpete, Bogor City, it is not yet varied. Therefore, in the learning process, it is necessary to develop learning media assisted by Qr Code so that learning becomes more interesting and varied. The study was aimed at developing and finding out the feasibility of Pop Up Book Media Assisted by Qr Code on Traditions and Culture of the Community Around Me. This study is a Research and Development (R&D) study with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) research method. The data collection technique in this study used an instrument sheet in the form of a questionnaire. Product testing was carried out by media experts, language experts, lecturer material experts and teacher material experts. The assessment results from media experts were 100%, language experts 100%, lecturer material experts 98.3%, and teacher material experts 96.6% which means it is very feasible to be implemented. and based on a limited trial conducted on 25 class IV A students, the percentage score was 97.0%, which means that the development of Pop Up Book Learning Media Assisted by QR Codes on the Traditions and Culture of the Community Around Me is very suitable for use in the learning process and can increase students' learning motivation.